The Scholarship of Syed Sharafat Ali Naushahi: An Introduction - Hassan Naushahi (بازیافت, 2025)
Syed Sharafat Naushahi was a renowned and distinguished intellectual of Urdu,Persian,Arabic and Punjabi languages. He was also sage, poet, historian, researcher, translater and calligrapher of his age. His literary specification and writing services regarding saints are the glittering evedences of his knowledge. History of Mysticism was his special area of interest. In an art of History Sharief ul Tawarikh  is his representative book. His beaming efficiency in the field of History and Literature was not the ralic of any institution but it was the miracle of the teaching of any accomplished Scholar. He opened a new world of discussion of research in the field of Urdu and punjabi langauges. He always kept in mind the research honesty and rules of traditions and attestification.He merely not only narrates the stories but also visualizes the incentives and effects of those incidents. All his books e.g Sharief ul Tawarikh, Tarekh i Abbasi, Tazkara Shuray Naushahia, Muwaz i Naushah Peer, Chahar Bahar(Translation), Gunj ul Asrar(Editing), IntiKhab i Gunj Sharief(Editing) represents his research abilities.